Clinical observations, environmental parameters, and gut microbiota alterations associated with gas bubble disease in the endangered Anji salamander (Hynobius amjiensis) - Haiyan Dong; Minglan Dong; Xiaolu Jin; Zhedong Lang; Xianting Wang; Jiabao Xu; Zixing Hu; Xiang Xu (Frontiers in Veterinary Science, 2026)
Gas bubble disease (GBD) is a non-infectious disease caused by the supersaturation of total dissolved gas (TDG) in aquatic environments, which can damage multiple tissues and organs in aquatic animals and be potentially fatal in severe cases. This study reports, for the first time, clinical symptoms resembling GBD in wild larvae of the endangered Anji salamander ( Hynobius amjiensis ). By combining clinical observations, habitat water quality testing, and 16S rRNA sequencing, we investigated the ecological drivers of this disease and its impact on the host’s fecal microbial community. Affected individuals exhibited severe subcutaneous and abdominal emphysema, buoyancy abnormalities, and anorexia; these symptoms resolved spontaneously within 24–72 h after transfer to stable water bodies. Puddles where cases occurred exhibited severe eutrophication and massive algal blooms, leading to extreme TDG supersaturation, primarily driven by dissolved oxygen. Furthermore, the species evenness of the fecal microbiota in the affected group showed a decreasing trend, with a massive loss of core commensal bacteria, while the relative abundance of the opportunistic pathogen Aeromonas increased abnormally. These findings indicate that eutrophication-driven physicochemical abnormalities in water bodies may be the primary environmental stressors inducing GBD, while the disease itself may disrupt the organism’s homeostasis, further triggering secondary dysbiosis of the gut microbiota. This study provides a reference for understanding the ecologically driven mechanisms of non-infectious diseases in wild amphibians, as well as for the management and conservation of aquatic environments in the habitats of endangered amphibian species.